Cochlear Implant Insertion Depth Prediction: A Temporal Bone Accuracy Study. Issue 10 (December 2018) - Anschuetz, Lukas; Weder, Stefan; Mantokoudis, Georgios; Kompis, Martin; Caversaccio, Marco; Wimmer, Wilhelm
Abstract : Hypothesis: The aim of this study was to present and validate the accuracy of a method to predict the required cochlear implant (CI) electrode array length for a specific angular insertion depth (AID). Background: The human cochlea exhibits remarkable interindividual morphological differences. The prediction of the required array length for a specific AID can help to improve the outcome of cochlear implant surgery. Methods: We estimated the linear insertion depth required for an angular insertion of 540 degrees using computed tomography images of 16 temporal bone specimens (eight Thiel fixed, eight formalin fixed). Free fitting electrode arrays were marked accordingly and inserted through a custom-made insertion guide tube. The achieved AIDs were assessed using postoperative micro-computed tomography scans. Results: In the Thiel specimens, the difference between the aimed depth of 540 degrees and achieved insertion depth was small (average 529 degrees, p = 0.076), with a mean prediction error of –11 degrees (maximum 30 degrees), indicating a small underestimation. By contrast, we observed early resistance during the insertions in the formalin specimens (average 409 degrees, p < 0.0001), resulting in a mean error of −131 degrees and bending of the electrode array in the cochlear basal turn in four of eight specimens. Conclusion: The equation presented in this study for calculating linear insertion depths can be helpful for the selection of adequate electrode array lengths in a clinical setting. The Thiel conservation is a highly suitable model for cadaveric electrode insertion studies. A free online calculator is available athttp://www.hno.insel.ch/de/forschung/ci_estimator/ .